2018
DOI: 10.3389/fimmu.2018.00267
|View full text |Cite
|
Sign up to set email alerts
|

Acquired Natural Killer Cell Dysfunction in the Tumor Microenvironment of Classic Hodgkin Lymphoma

Abstract: An understanding of interactions within the tumor microenvironment (TME) of classic Hodgkin lymphoma (cHL) has helped pave the way to novel immunotherapies that have enabled dormant and tumor-tolerant immune cells to be reactivated. The immunosuppressive nature of the TME in cHL specifically inhibits the proliferation and activity of natural killer (NK) cells, which contributes to tumor immune-escape mechanisms. This deficiency of NK cells begins at the tumor site and progresses systemically in patients with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(56 citation statements)
references
References 110 publications
1
53
0
2
Order By: Relevance
“…A phase I study for relapsed/refractory AML patients using MEN1112 (NCT02353143) is expected to shed light on its tolerability and potential future use in single/combination therapy. NK cells are largely excluded from the TME in HL, and peripheral blood and tumor infiltrating NK cells from HL patients are severely impaired (237). Therefore, enhancing their activity in HL may greatly benefit treatment.…”
Section: Mabs In Clinical Trials-targeting Tumor Ligands For Optimizamentioning
confidence: 99%
“…A phase I study for relapsed/refractory AML patients using MEN1112 (NCT02353143) is expected to shed light on its tolerability and potential future use in single/combination therapy. NK cells are largely excluded from the TME in HL, and peripheral blood and tumor infiltrating NK cells from HL patients are severely impaired (237). Therefore, enhancing their activity in HL may greatly benefit treatment.…”
Section: Mabs In Clinical Trials-targeting Tumor Ligands For Optimizamentioning
confidence: 99%
“…The immunosuppressive nature of the TME in cHL specifically depends on the inhibition of the proliferation and activity of the natural killer (NK) cells, which contribute to the tumour immune escape mechanisms. Locally, the HRS cells and the cells from the TME express ligands for inhibitory receptors on NK cells, including HLA‐E, HLA‐G, and PD‐L1 . In addition, the infiltrating lymphocytes in the micro‐environment of solid tumour, mainly CD8 + T cells, recognize the tumour antigen by MHC‐I on APCs.…”
Section: The Immune Escape Mechanism Of Hrs Cells In Chlmentioning
confidence: 99%
“…In patients with HL, studies have shown that: (1) the immunosuppressive nature of the TME speci ically inhibits proliferation and activity of NK cells, (2) malignant Reed-Sternberg cells and other components of the TME express ligands to inhibit NK cells, and (3) although NK cell de iciency begins at the tumor site, ultimately it progresses systematically in patients with advanced disease as the secretion of cytokines and chemokines mediates the systemic immunosuppression. Thus, strategies to reactivate NK cell function or those aimed at blocking the evasive mechanisms displayed by the TME may ultimately identify new immunotherapeutic targets [230,231]. In patients with HL, CD 123 (IL-3Rα) is frequently expressed by malignant cells and the combination of NK cells and the fully humanized anti-CD 123 monoclonal antibody (CSL362) represents a promising future therapeutic strategy [144].…”
Section: Nk Cells In Lymphomasmentioning
confidence: 99%